PENGEMBANGAN e-MODUL BERBASIS REALISTIC MATHEMATIC EDUCATION (RME) PADA PEMBELAJARAN MATEMATIKA KELAS IV SEKOLAH DASAR - Irma Nur Anisah; Agus Susanta; Puspa Djuwita (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to develop an RME-based e-module product, describe the feasibility, and practicality of RME-based e-module development in Mathematics learning for FPB and KPK grade IV Elementary School materials. This study uses a research and development (R&D) type that adapts the ADDIE model, namely analysis, design, development, implementation, and evaluation. Data collection techniques used are interviews with teachers to find out the needs, and teacher responses. In addition, it also uses student questionnaires to determine student needs and responses to RME-based e-modules in online mathematics learning. The data obtained were analyzed based on the Aiken's V Coefficient. This development research resulted in a product in the form of an RME-based e-module in Mathematics learning for FPB and KPK grade IV Elementary Schools. The feasibility of the material, language and media (presentation) is declared feasible, practicality is declared very practical judging from the teacher's response, and the student's response.